2020
DOI: 10.1371/journal.pone.0231038
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitors: Better outcomes among advanced cutaneous head and neck melanoma patients

Abstract: The aim of this study was to investigate if the treatment outcomes of checkpoint inhibitors (CPI) in patients with advanced-stage skin head and neck melanoma (HNM) differs from outcomes in patients with non-HNM. Design A retrospective cohort study of patients with unresectable AJCC stage III and stage IV, who received CPI between 2010 and 2017. Participants Overall, 122 unresectable AJCC stage III and metastatic stage IV melanoma adult patients were treated with CPI during the study period (consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…The findings of this study underscore a significant improvement in the survival of this patient population, with the median survival increasing from a historical 10 months to over 40 months in the present day 20 . This is further corroborated by Hirshoren et al, who also reported superior results of IT in advanced H&N melanoma compared to cutaneous melanoma of limbs and trunk (mOS of 60.2, 51.2, and 53.4, respectively) 21 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings of this study underscore a significant improvement in the survival of this patient population, with the median survival increasing from a historical 10 months to over 40 months in the present day 20 . This is further corroborated by Hirshoren et al, who also reported superior results of IT in advanced H&N melanoma compared to cutaneous melanoma of limbs and trunk (mOS of 60.2, 51.2, and 53.4, respectively) 21 …”
Section: Discussionsupporting
confidence: 84%
“…20 This is further corroborated by Hirshoren et al, who also reported superior results of IT in advanced H&N melanoma compared to cutaneous melanoma of limbs and trunk (mOS of 60.2, 51.2, and 53.4, respectively). 21 Recent pivotal trials have shown that combination IT has a numerical advantage in mOS over anti-PD-1 monotherapy, although the difference was not statistically significant. 5 In our study cohort, only a small portion of BRAF positive patients were treated with TT in the first line setting.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as ipilimumab are designed to target CTLA-4 and enhance anti-tumor immunity by removing this block to T-cell activation ( Soldevilla et al, 2019 ). Clinical trials have demonstrated the efficacy of CTLA-4 inhibitors in the treatment of cancers, including melanoma ( Hirshoren et al, 2020 ).…”
Section: Advantages and Limitations Of Gene Therapy In The Context Of...mentioning
confidence: 99%
“…The first antibodies that progressed into clinical trials after showing promising results in cancer treatment were ipilimumab, tremelimumab and quavonlimab, three anti-CTLA-4 antibodies. Ipilimumab is clinically employed for treatment of unresectable stage III/IV metastatic melanoma and as adjuvant therapy for radically resected "high-risk" melanoma patients [ 46 , 47 , 48 , 49 ], while tremelimumab and quavonlimab are currently being tested in clinical trials for safety and efficacy determination.…”
Section: Immune Checkpoint Blocker Delivery With Nanocarriersmentioning
confidence: 99%